Filogenia del complejo Heterotaxis Lindl. (Maxillariinae): evolución de la arquitectura vegetativa y los síndromes de polinización - Ojeda, Isidro (Universidad de Costa Rica, 2016)
Heterotaxis Lindl. comprises about 11 primarily epiphytic species ranging from the southeastern U.S.A. (Florida) and the Greater Antilles to Brazil, with most of the species occurring in Central and South America. This complex is characterized by a sympodial growth habit, with short rhizomes, lateral- ly compressed oblong pseudobulbs (unifoliate), and subtended by various leaf-bearing sheaths